Antimicrobial activity and DNA fingerprinting of bacteriocinogenic Pediococcus acidilactici through RAPD-PCR (2004)
The antimicrobial activity and DNA fingerprint of Pediococcus acidilactici AA5a, a bacteriocin-producing isolate from fermented rice-fish mixture (burong isda), were compared with a reference bacteriocin-producing strain, P. acidilactici S3. Both inhibited strains of Lactobacillus, Pediococcus, Enterococcus, Bacillus, Leuconostoc and Listeria spp. Out of 8 randomly amplified polymorphic DNA (RAPD) primers tested for polymerase chain reaction (PCR) assays to fingerprint the isolates, 5 primers showed identical PCR profiles between the two strains. On the other hand, 3 RAPD primers and a 16S rRNA-based primer differentiated them. One primer that showed identical PCR results and another one that differentiated the isolates were chosen to fingerprint other strains of Pediococcus and other Gram-positive bacteria. From the results of RAPD-PCR assays, dendrograms were constructed to show the similarity of relationships among the investigated strains derived through the Unweighted Pair Group Method, Arithmetic mean (UPGMA) analysis. P. acidilactici was differentiated from other P. acidilactici strains and other species under the genus Pediococcus.
Keywords: Metabolites; DNA fingerprinting; Bacteriocins